The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/pr900711j
|View full text |Cite
|
Sign up to set email alerts
|

Systems Metabolic Effects of a Necator americanus Infection in Syrian Hamster

Abstract: Hookworms (Ancylostoma duodenale and Necator americanus) are blood-feeding intestinal nematodes that infect ∼700 million people worldwide. To further our understanding of the systems metabolic response of the mammalian host to hookworm infection, we employed a metabolic profiling strategy involving the combination of 1 H NMR spectroscopic analysis of urine and serum and multivariate data analysis techniques to investigate the biochemical consequences of a N. americanus infection in the hamster. The infection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 52 publications
(139 reference statements)
1
23
0
Order By: Relevance
“…haematobium eggs in the GIT [ 17 ] provides in theory, an opportunity for direct interaction between the parasites and the gut flora. Studies in Syrian hamsters [ 18 ], have shown shifts in the composition of the gut microbiota during helminth infection, while a recent study in humans reported that people infected with the intestinal helminths of the genus Trichuris , had greater gut bacteria species richness compared to uninfected people [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…haematobium eggs in the GIT [ 17 ] provides in theory, an opportunity for direct interaction between the parasites and the gut flora. Studies in Syrian hamsters [ 18 ], have shown shifts in the composition of the gut microbiota during helminth infection, while a recent study in humans reported that people infected with the intestinal helminths of the genus Trichuris , had greater gut bacteria species richness compared to uninfected people [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Leukocytes are known to contain high amounts of taurine, which can have a role in acute or chronic immune responses as an antioxidant and cytoprotectant. 36 Therefore, reduced leukocyte infiltration in zinc-deficient infected mice may reflect lower systemic availability of taurine and could help explain the reduced excretion of taurine related metabolites when compared with the house chow-fed infected mice. These metabolomic findings may help to explain the chronic effects of infection seen in zinc-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…This was broadly similar to the effects of infection by S. mansoni [28][29], suggesting such effects as a universal consequence of schistosomiasis. Amongst the microbial related metabolites, elevations of 4-cresol glucuronide and PAG and depressed levels of hippurate appeared to be common for the hosts infected with helminths [28][29] and intestinal nematodes [54]. Further research is required to determine the fine-grained alterations in the microbial community associated with infection, which will enhance our understanding of three-way host-parasite-microbiota interactions.…”
Section: Discussionmentioning
confidence: 99%